2018
DOI: 10.1186/s40780-018-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of sodium azulene sulfonate L-glutamine for managing chemotherapy-induced oral mucositis in cancer patients: a prospective comparative study

Abstract: BackgroundThe efficacy of sodium azulene sulfonate L-glutamine (GA) in treating oral mucositis caused by the administration of anticancer agents has not been previously elucidated. Therefore, this prospective comparative study was conducted to evaluate the efficacy of GA in treating oral mucositis caused by chemotherapy regimens involving fluorinated pyrimidine anticancer drugs.MethodsThe subjects of this study were patients with oral mucositis of grade 2 or higher while on outpatient chemotherapy regimens inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Additionally, a large prospective cohort study has found oral glutamine to be effective in preventing OM [77]. Likewise, a non-blinded RCT in solid cancer patients treated with CT reported that glutamine formulated as sodium azulene sulfonate L-glutamine was effective in preventing OM [78].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large prospective cohort study has found oral glutamine to be effective in preventing OM [77]. Likewise, a non-blinded RCT in solid cancer patients treated with CT reported that glutamine formulated as sodium azulene sulfonate L-glutamine was effective in preventing OM [78].…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that among twelve guaiazulene-3-carboxylates, two alkoxyl guaiazulene-3carboxylates [6,7] showed higher tumor-specificity than five alkyl [1][2][3][4][5] and two hydroxyalkyl [8,9] guaiazulene-3carboxylates and three aminoalkyl guaiazulene-3-carboxylate carboxamides [10][11][12] (Table I). Both [6,7] showed higher TS value than CDDP and CBDCA, and having comparable PSE value with 5-FU (Table I).…”
Section: Discussionmentioning
confidence: 96%
“…Methyl guaiazulene-3-carboxylate [1], ethyl guaiazulene-3-carboxylate [2], n-propyl guaiazulene-3-carboxylate [3], isopropyl guaiazulene-3carboxylate [4], n-butyl guaiazulene-3-carboxylate [5], 2methoxyethyl guaiazulene-3-carboxylate [6], 2-ethoxyethyl guaiazulene-3-carboxylate [7], 2-hydroxyethyl guaiazulene-3carboxylate [8], 2-(2-hydroxyethoxy)ethyl guaiazulene-3-carboxylate…”
Section: Synthesis Of Guaiazulene-3-carboxylate Derivativesmentioning
confidence: 99%
See 2 more Smart Citations